Titania nanotubes with aminated reduced graphene oxide as efficient photocatalysts for antibacterial application under visible light - Kyoung-Suk Moon; Ji-Myung Bae; Eun-Joo Choi; Seunghan Oh (Scientific Reports, 2025)
Abstract Titania and reduced graphene oxide (rGO) are well-known materials with excellent photocatalytic properties, but research on the photocatalytic-based antibacterial effects of their combination remains limited. This study explored the suitability of titania nanotubes (TiO2 NTs) combined with rGO and two terminal functional groups (nonfunctional and aminated groups (NH2)) as efficient photocatalysts for antimicrobial applications under visible light irradiation. Field-emission scanning electron microscopy observations revealed that rGO covered the entire surface of the TiO2 NTs. Tauc plots calculated from the spectra of diffuse reflectance spectroscopy showed that the band gaps of the nonfunctional and amine functional groups of rGO-coated TiO2 NTs were 2.40 and 2.21 eV, respectively. Therefore, all rGO-coated TiO2 NTs exhibited photocatalytic activity under 470 nm visible light irradiation. An antibacterial colony forming unit test using S. aureus and P. aeruginosa, and two enzymatic activity tests (superoxide dismutase and catalase) on the same bacteria, showed that the aminated rGO-coated TiO2 NTs showed excellent antibacterial activity under 470 nm visible-light irradiation compared to nonfunctional rGO-coated TiO2 NTs and uncoated TiO2 NTs groups. In addition, the MTT assay showed that the aminated rGO-coated TiO2 NTs enhanced cell viability after visible light irradiation. Therefore, the combination of aminated rGO-coated TiO2 NTs and visible-light-triggered photocatalytic activity has significant potential for expressing antibacterial properties in dental applications.